Constructing the Teacher Self: The Role of Initial Teacher Education in Shaping Pre Service English Teacher Professional Identity - Islam, Syaiful; Fabela, Ifa Aprilia; Qomariyah, Khoirotul; Faizah, Umi Nur; Karomah, Wardatul (Universitas Nurul Jadid, 2025)
This study explores how initial teacher education (ITE) influence professional identity construction of pre service English teachers in rural Islamic-based schools in Indonesian context. Employing multiple case study design with six pre service teachers, the research utilized semi-structured interview. Findings reveal that initial motivation for teaching are varied, inspired by past educators, yet frequently accompanied by an underestimation of teaching complexity. Academic training provides foundational knowledge, but the practicum serves as a critical “reality shock,” profoundly reshaping perceptions and shifting focus from content delivery to a holistic understanding of teaching. The unique rural and religious context actively compels pedagogical adaptation, influence role perception and facilitate the integration of personal values. Support system, mentorship and peer networks are crucial for confidence development. The understanding of “being teacher” evolves from a task-oriented role to a multi-faceted agent committed to students’ holistic development. These insights underscore the need for ITE programs to enhance practicum design, strengthen mentorship and foster resilience and adaptability to support comprehensive professional identity development of future teachers.